Six-fold increase of atmospheric pCO2 during the Permian–Triassic mass extinction - Yuyang Wu (Nature Portfolio, 2021)
The Permian–Triassic mass extinction was accompanied by a massive release of carbon into the ocean-atmosphere system, but the magnitude of change is not well known. Here, the authors present a new record of C3 plants from southwestern China which shows that atmospheric pCO2 increased by a factor of six during this event.